Production mono-diglyceride (MDG) from refined deodorized palm oil (RBDPO) by enzymatic process - E., Julianti (2023)
The objective of this research was to know the best reaction time of glycerolysis processing. Esterification of glycerol and RBDPO using lipase as catalyst was used to synthesize MDG. Eight batch reactions consisting of refined bleached deodorized palm oil (RBDPO), glycerol, and commercially lipase were carried out. Production yield, glyceride (MG, DG and TG) composition, Free Fatty Acid (FFA), peroxide value, iodine value, melting point, and HLB value were used as parameters. Monoglyceride (MG), diglyceride (DG) and triglyceride (TG) composition in the product were analyzed using thin layer chromatography (TLC) and TLC Scanner. The best reaction time identified at about 24 hours. Under this condition production yield was 78,70% with MG, DG, TG was 40,16%; 49,92%; 10% respectively. The Analysis of physicochemical properties showed that the average FFA, peroxide value, iodine value, melting point, and HLB value were 0.16%, 5.33 meq/kg, 46.33, 59.83oC, and 8.97, respectively. The product melting point was higher and the iodine value was lower than RBDPO i.e. 53.5˚C and 53.99, respectively with FFA content was 0.14%.